Usefulness of automatic assessment for longitudinal strain to diagnose wild-type transthyretin amyloid cardiomyopathy - Hiroki Usuku; Eiichiro Yamamoto; Daisuke Sueta; Kanako Imamura; Fumi Oike; Kyohei Marume; Masanobu Ishii; Shinsuke Hanatani; Yuichiro Arima; Seiji Takashio; Seitaro Oda; Hiroaki Kawano; et al. (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: Left ventricular (LV) apical sparing by transthoracic echocardiography (TTE) has not been widely accepted to diagnose transthyretin amyloid cardiomyopathy (ATTR-CM), because it is time consuming and requires a level of expertise. We hypothesized that automatic assessment may be the solution for these problems. Methods-and-Results: We enrolled 63 patients aged ≥70 years who underwent 99mTc-labeled pyrophosphate (99mTc-PYP) scintigraphy on suspicion of ATTR-CM and performed TTE by EPIQ7G, and had enough information for two-dimensional speckle tracking echocardiography at Kumamoto University Hospital from January 2016 to December 2019. LV apical sparing was described as a high relative apical longitudinal strain (LS) index (RapLSI). Measurement of LS was repeated using the same apical images with three different measurement packages as follows: (1) full-automatic assessment, (2) semi-automatic assessment, and (3) manual assessment. The calculation time for full-automatic assessment (14.7 ± 1.4 sec/patient) and semi-automatic assessment (66.7 ± 14.4 sec/patient) were significantly shorter than that for manual assessment (171.2 ± 59.7 sec/patient) (p < 0.01 for both). Receiver operating characteristic curve analysis showed that the area under curve of the RapLSI evaluated by full-automatic assessment for predicting ATTR-CM was 0.70 (best cut-off point; 1.14 [sensitivity 63%, specificity 81%]), by semi-automatic assessment was 0.85 (best cut-off point; 1.00 [sensitivity, 66%; specificity, 100%]) and by manual assessment was 0.83 (best cut-off point; 0.97 [sensitivity, 72%; specificity, 97%]). Conclusion: There was no significant difference between the diagnostic accuracy of RapLSI estimated by semi-automatic assessment and that estimated by manual assessment. Semi-automatically assessed RapLSI is useful to diagnose ATTR-CM in terms of rapidity and diagnostic accuracy.